FEASIBILITY DEMONSTRATION OF TECHNOLOGIES FOR THE DEVELOPMENT OF PINE BURNT WOODS WITH THE AIM OF REESTABLISHMENT OF THE PINE STAND FROM THE SEEDS REMAINING IN TREE CROWNS AFTER A LOW FIRE - Shirnin, Yuri; Denisov, Sergey; Shirnin, Aleksandr (Journal of Applied Engineering Science, 2016)
The following research deals with the issues of technologies of forest reproduction development of burnt pine trees stands. Middle-aged, ripening and mature pine stands, damaged by creeping fire, keep a stock of germinating seeds. The amount of pine seeds is sufficient for natural development of deciduous-pine growths under such conditions. А variety of machine systems and technologies are provided in order to secure available seed stock during the process of logging marketable timber within burnt wood stand areas. Moreover, these systems would facilitate felling areas of burnt wood with advance growth.